FROM THE FIELD TO THE MIND: HOW SPORT INFLUENCES MENTAL HEALTH - Muktifada Matilda, Arthagina; Adelia Intan Wulandari, Bernadetta Prisca; Darmanto, Darmanto (PARADIGM : Journal Of Multidisciplinary Research and Innovation, 2025)
The current research tries to explore the impact of sport on mental health. This study is descriptive qualitative research in which it uses previous studies as data of this research. The findings reveal participation in exercise, particularly within a social context like sports, significantly can improve emotional control, reduce anxiety, and boost self-esteem. Social interactions, whether face-to-face or digital, enhance resilience and promote positive mental health by providing a strong support system. Regular physical activity not only strengthens physical health but also fosters social relationships, enhancing cognitive abilities such as concentration and decision-making. Furthermore, a holistic approach to integrating physical, mental, and social dimensions is essential for overall life satisfaction. This research emphasizes the importance of exercise, social connections, and mindfulness practices in promoting mental health and improving self-confidence, highlighting the interconnectedness of physical activity and mental well-being.